ANALISIS KOMODITI BASIS SUBSEKTOR TANAMAN PERKEBUNAN DI KABUPATEN PARIGI MOUTONG - Widhana, Ketut; Rauf, Rustam Abd.; Laapo, Alimudin (AGROTEKBIS, 2019)
This research aims to identify the wide of area and the commodity of sub sector base of plantation crops in Parigi Moutong Regency. This research was conducted in Parigi Moutong. This location was selected by purposive sampling with considering that the Parigi Moutong Regency has high contribution on the level of plantation crops in central Sulawesi Province. Data used is secondary data as data of production data and the wide of plantation crops of 2011 to 2015. Analysis method used is locatin quotient (LQ) analysis. The result of this research showed that the average of LQ based on the wide of area, cocoa commodity is as a base commodity LQ>1 and the value is 1,52, the value of LQ based on the production of three commodity cloves, LQ 1.31, the value of coconut commodity is LQ 1.46 and cacao commodity is LQ 1.58.